Design, synthesis and antiviral activity of entry inhibitors that target the CD4-binding site of HIV-1 - Curreli, Francesca (2012)
The CD4 binding site on HIV-1 gp120 has been validated as a drug target to prevent HIV-1 entry to cells. Previously, we identified two small molecule inhibitors consisting of a 2,2,6,6-tetramethylpiperidine ring linked by an oxalamide to a p-halide-substituted phenyl group, which target this site, specifically, a cavity termed “Phe43 cavity”. Here we use synthetic chemistry, functional assessment and structure-based analysis to explore variants of each region of these inhibitors for improved antiviral properties. Alterations of the phenyl group and of the oxalamide linker indicated that these regions were close to optimal in the original lead compounds. Design of a series of compounds, where the tetramethylpiperidine ring was replaced with new scaffolds, lead to improved antiviral activity. These new scaffolds provide insight into the surface chemistry at the entrance of the cavity and offer additional opportunities by which to optimize further these potential-next-generation therapeutics and microbicides against HIV-1.